Correlation Analysis of the Bacterial Community and Wood Properties of Populus × euramericana cv. “74/76” Wet Heartwood - Fan, Jianmin; Wang, Shijie; Ding, Changjun; Ma, Changming; Chen, Xinghao; Wang, Jinmao; Yang, Minsheng; Su, Xiaohua (Frontiers in Microbiology, 2022)
Wetwood disease of poplar limits the processing and manufacturing of poplar, and the pathogenic bacteria of wet heartwood are poorly known. We used high-throughput sequencing methods to analyze the bacterial community of the heartwood, sapwood, root tissue, and rhizosphere soil of Populus × euramericana cv. “74/76” (poplar 107) in wetwood trees and healthy trees to explore the cause of poplar wetwood disease. Bacterial diversity and community structure were analyzed, and the correlation between wood properties and bacterial relative abundance was analyzed to explore their relationship. Two alpha-diversity indices of endophytic bacteria in the heartwood of wetwood trees were significantly (p < 0.05) lower than that in the heartwood of healthy trees, and the community structure between the two types of trees was significantly different. No significant differences in the alpha-diversity indices nor community structure were observed in the sapwood, root tissue, or rhizosphere bacterial community of diseased and healthy trees. The distribution of dominant bacteria genus in the heartwood of diseased and healthy trees differed. Proteiniphilum, Actinotalea, and Methanobacterium were the dominant genera in diseased trees’ heartwood. Proteiniphilum, Dysgonomonas, and Bacteroides were the dominant genera in healthy trees’ heartwood. The relative abundance of Proteiniphilum, Actinotalea, and Methanobacterium was significantly higher in the heartwood of wetwood trees than those of healthy trees. A db-RDA analysis found that these three bacterial genera were positively correlated with the rate of wet heartwood. These three bacterial genera may be the main pathogens causing poplar wetwood disease.